Toll-like Receptors in Ovarian Cancer as Targets for Immunotherapies - Muccioli, Maria; Benencia, Fabian (Frontiers in Immunology, 2014)
In the last decade, it has become apparent that Toll-like Receptor (TLR) signaling can play an important role in ovarian cancer progression. Interestingly, TLR activation in immune cells can help activate an anti-tumor response, while TLR signaling in tumor cells themselves is often associated with cancer-promoting inflammation. For example, it has been shown that TLR activation in dendritic cells can result in more effective antigen presentation to T cells, thereby favoring tumor eradication. However, aberrant TLR expression in ovarian cancer cells is associated with more aggressive disease (likely due to recruitment of pro-tumoral leukocytes to the tumor site), and has also been implicated in resistance to mainstream chemotherapy. The delicate balance of TLR activation in the tumor microenvironment in different cell types altogether help shape the inflammatory profile and outcome of tumor growth or regression. With further studies, specific activation or repression of TLRs may be harnessed to offer novel immunotherapies or adjuvants to traditional chemotherapy for some ovarian cancer patients. Herewith we review recent literature on basic and translational research concerning therapeutic targeting of TLR pathways for the treatment of ovarian cancer.